Intensified solvent extraction and separation of cobalt from Ni-rich leaching solution in impinging stream-rotating packed bed contactor. Issue 5 (2nd September 2020) - Chang, Jun; Jia, Fukang; Mumford, Kathryn A.; Yang, Xiaohong; Xie, Zinan
ABSTRACT: This work describes the separation of Ni and Co from a real feed solution in chloride media with high Ni content. The extractant used was P507 (2-ethylhexyl phosphoric acid-2-ethylhexyl ester) in a laboratory scale Impinging Stream–Rotating Packed Bed (IS-RPB) contactor. Key variables including feed solution pH, extractant concentration, saponification degree, high gravity level and total volumetric flow rate of fluids amongst other variables were examined. A McCabe–Thiele diagram of the extraction stage predicted that at a total volumetric flow rate of 90 L/h, feed solution pH of 5, saponified P507 concentration of 25% and high gravity of 83, almost 99% of cobalt, would be extracted within three stages. With regard to the scrubbing results, the co-extracted nickel was scrubbed efficiently from the loaded organic solution using a mixture of 0.02 M CoCl2 and 0.5 M hydrochloric acid solution, The purified Co solution was achieved after stripping the loaded-organic phase with 1 M HCl. The maximum value of the overall volumetric mass transfer coefficient for the IS-RPB extractor was found to be 0.16 s −1 which was superior to that of conventional extractors such as mixer-settler and centrifugal extractors, providing strong confidence for its industrial application.